COMPARATIVE AND CONTRADICTIVE FIGURATIVE LANGUAGE IN LES MISERABLE BY VICTOR HUGO: A SEMANTICS ANALYSIS - Robby Satria (Jurnal Pendidikan Teknologi Informatika dan Sains, 2021)
This research discusses the application of Semantics theory proposed by Leech. it discusses the occurrence of figurative language in Victor Hugo's work entitled “Les Miserable” through a semantic approach. The purpose of this research is to analyse the figurative and comparative language found in the novel "Les Miserables" by Victor Hugo. The research applies the semantic theory by Leech's (1981) especially for connotative meaning and supported by figure of speech theory by Dancygier and Keraf (1994) for its figurative language. Qualitative method is applied in this study and library research as a technique used to collect data. The researcher analyses the data from the figurative language of the novel. Comparative figurative language found are personifications, similes, hyperboles, litotes, and paradoxes. The findings of this study shows that there are 55 figurative languages ​​identified in the novel. The researcher found that most figurative languages used by Victor Hugo is comparative one. Key words: semantics, connotative meaning, figurative language.